Agricultural change and rural poverty: variations on a theme by Dharm Narain - Mellor, John W.; Desai, Gunvant M. (International Food Policy Research Institute, 1985)
During the past two decades there has been increasing concern that the development strategies of the 1950s and 1960s would neither eliminate nor even greatly reduce poverty even as the pervasive nature of that poverty became more widely recognized. This increase in concern conincided with the drama of the major biological breakthroughs in food production associated with the "green revolution." A debate began on whether there was a causal relation between the technology of the green revolution and the incidence of rural poverty. The conclusion of this debate is of importance not only because food is vital but because population growth is placing greater pressure on existing food supplies and because limited land area is shifting the means of expanding food production towards yield-increasing technology.